Penilaian Status Gizi, Edukasi dan Pengenalan Inovasi Pangan sebagai Upaya Pencegahan Stunting pada Ibu Hamil di Desa Rejosari Kabupaten Demak - Fina Dwi Aryanti; Nikmatul Luailiya; Nana Misrochah; Nur Kiki Patmawati; Eka Bima Christiana; Muslimah Hasanah (Faculty of Engineering, Universitas Semarang, 2024)
Stunting is malnutrition that occurs gradually and is prolonged. In general, according to Riskesdas (2018), the prevalence of stunting in Indonesia is 30.8%, and in Demak 26.1%. Meanwhile in Rejosari Village. Based on data from local midwives, there are 15 stunted children in Karangawen, Demak. The purpose of dedication is as a preventive measure so that the incidence of stunting under five in Rejosari Village, Demak Regency does not increase. The implementation began with a health stand, and interactive discussions, and ended with a cooking demonstration for pregnant women. The activity began with an anthropometry stand, continued with education on the importance of the role of 1000 HPK, questions, and answers, and ended with a demonstration on making Moringa Chicken Tofu Balls. The results of the